‘The Peculiar Genius of Private-Law Systems’: Making Room for Religious Commerce - Michael A. Helfand (Washington University Law Review, 2020)
Religious commerce has long sat uncomfortably at the nexus of public law and private law. On the one hand, such transactions invariably have garden-variety commercial objectives, which are best achieved and regulated through the law of tort, contract, and property. And yet the intermingled religious aspirations of the parties often inject constitutional concerns that muddy the waters. To navigate these challenges, the Supreme Court famously embraced the neutral principles of law framework, which encouraged parties to draft private law agreements using secular terminology. Thus, while the Establishment Clause provided the outer boundaries for what was legally possible, the neutral principles of law framework made space for religion under the umbrella of private law. This equilibrium between public and private law, however, has become increasingly unsettled. As the permutations of contracting for religion have proliferated, courts and scholars have searched for tools to regulate what they view as problematic outcomes. At the core of such criticisms is an instinct that judicial enforcement of privatized religious obligation—whether in the form of religious contracts generally or religious arbitration specifically—undermines a principled commitment to separation of church and state. In turn, courts and scholars have reached into their constitutional toolboxes, searching for legal doctrines that might eliminate the kinds of outcomes they view as offending fundamental constitutional principles. The goal of this Article is to argue that this public law instinct—the notion that regulating the field of religion and private law is best achieved through the expansion of constitutional prohibitions—is deeply misguided. And this is true not only for standard religious commerce, but also—and especially—for the religious commerce safety valve, religious arbitration. Ultimately, successfully merging religion and private law requires promoting doctrines that, on the one hand, address legitimate concerns, but do so without eliminating the very legal terrain made possible by the neutral principles of law framework. Failure to do so—and reflexively reaching into our constitutional toolbox—leaves both courts and scholars without the tools they need to meet these legal challenges.
Keywords: Religious commerce; Neutral principles of law framework; Establishment clause; Private law; Religious arbitration; Religious contracts